PEMBELAJARAN KOOPERATIF MODEL YURISPRUDENTIAL INQUIRY UNTUK MENINGKATKAN PEMAHAMAN BUDAYA DEMOKRASI MENUJU MASYARAKAT MADANI - Zubaidah Zubaidah; Pargito Pargito; Adelina Hasyim (Faculty of Teacher Training and Education, University of Lampung, 2013)
The Purpose of this study is to describe the application of learning models Yurisprudential Inquiry to improve the understanding of civil society towards a democratic culture in class XI IPS 1 SMAN Baradatu. This study is an action research, Kemmis and Taggart besiklus covering planning, action, observation and reflection. Data collection instrument is to assign tasks on each end of the cycle and observations on the process of learning as well as an interview after learning activities. The results in the first cycle of student understanding reached 69,09 (48,39%), the second cycle increased to 73,25 (70,97%), and the third cycle increased to 75,90 (83,87%). Based on the results of this study concluded that the implementation of cooperative learning model Yurisprudential Inquiry to improve the understanding of civil society towards a democratic culture in class XI IPS 1 SMAN Baradatu.Keywords : classroom action research, PTK, cooperative learning yurisprudential inquiry model, democracy culture to reach madani people